Star clusters in the era of large surveys : Proceedings of Symposium 5 of JENAM 2010 - Alves, João; Moitinho, André (Astrophysics and Space Science Proceedings,, 2012)
The symposium "Star Clusters in the Era of Large Surveys" was held in Lisbon on Sep 9-10 during the JENAM 2010. It served as a platform for discussing what and how recent, on-going and planned large-area ground-based and space-based surveys can contribute to producing a major leap in this research field, which has a strong European history. Scientific topics addressed included: • Cluster searches • Clustered vs. isolated star formation, large-scale star formation, enrichment of the field population • Structure, populations and evolution of the Milky Way • Cluster dynamics (internal and within the Milky Way) • Variability of stars in clusters (from time-resolved surveys) • Analysis techniques for large samples • Archiving This proceedings book provides a snapshot of the ongoing discussion on the role of large surveys in star cluster research, and serves as a reference volume for the state-of-the art in the field.